2008
DOI: 10.1111/j.1365-2966.2007.12794.x
|View full text |Cite
|
Sign up to set email alerts
|

Nekhoroshev stability atL4orL5in the elliptic-restricted three-body problem - application to Trojan asteroids

Abstract: The problem of analytical determination of the stability domain around the points L4 or L5 of the Lagrangian equilateral configuration of the three‐body problem has served in the literature as a basic celestial mechanical model probing the predictive power of the so‐called Nekhoroshev theory of exponential stability in non‐linear Hamiltonian dynamical systems. All analytical investigations in this framework have so far been based on the circular restricted three‐body problem (CRTBP). In this work, we extend th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 31 publications
(34 reference statements)
0
33
0
Order By: Relevance
“…Most of the studies were devoted to the stability of Jupiter's Trojan asteroids (see e.g., Giorgilli and Skokos 1997;Levison et al 1997;Marzari and Scholl 2002;Efthymiopoulos and Sándor 2005;Robutel and Gabern 2006;Lhotka et al 2008), but other Trojans were also considered (Dvorak et al 2008b). Kinoshita and Nakai (2007) studied quasi-satellites of Jupiter in the 1:1 mean motion resonance.…”
Section: Introductionmentioning
confidence: 98%
“…Most of the studies were devoted to the stability of Jupiter's Trojan asteroids (see e.g., Giorgilli and Skokos 1997;Levison et al 1997;Marzari and Scholl 2002;Efthymiopoulos and Sándor 2005;Robutel and Gabern 2006;Lhotka et al 2008), but other Trojans were also considered (Dvorak et al 2008b). Kinoshita and Nakai (2007) studied quasi-satellites of Jupiter in the 1:1 mean motion resonance.…”
Section: Introductionmentioning
confidence: 98%
“…the studies of Rabe (1967); Bien & Schubart (1984); Lhotka et al (2008) and Érdi et al (2009) as well as many others. Ever since, extensive numerical studies have been undertaken to find the extension of the stability regions around the equilibrium points of the planets, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The mapping is defined on the 4 dimensional Poincaré surface of section, but given in its implicit form. Former studies (Lhotka et al 2008) showed that the radius of convergence of the proposed mapping method becomes limited to the librational regime of the asteroid's motion, if we expand the generating function to make the mapping explicit by series reversion. Therefore we applied a semi-analytical approach and introduced a simple root-finding algorithm to iterate the mapping at each iteration step without expanding it into explicit form; so we can preserve all possible dynamical behaviour of the mapping.…”
Section: Hadjidemetriou Mapping For Neptune's Trojan Asteroidsmentioning
confidence: 99%
“…A detailed description of the developement of the disturbing function in the 1:1 resonance with free parameters (m 1 , a , e , ω ) can be found e.g. in (Lhotka et al 2008), where an exponential stability estimate for the Trojan group of asteroids (e.g. Efthymiopoulos and Sándor 2005) was performed and generalized to be applicable also for different Solar system configurations.…”
Section: Hadjidemetriou Mapping For Neptune's Trojan Asteroidsmentioning
confidence: 99%